Sweden’s Migration Policy: From Openness to Control - Grzela, Joanna (Roczniki Nauk Społecznych, 2025)
The aim of the article is to analyze changes in Sweden’s migration policy. The research problem is formulated as a question: what factors caused this country to balance between humanitarian aid and the need to control migration since the end of World War II, until its decision to tighten the migration policy in 2024? The research hypothesis is this: the migration policy of Sweden in response to local and global migration challenges has changed from openness to full control of newcomers. The article uses the following research methods: literature review and historical, comparative, systemic and institutional-legal analysis. The scientific literature reviewed here is in Polish, English and Swedish, as well as online articles, statements and comments made by politicians concerning the nature of the events taking place at the time of writing this text.